2016
DOI: 10.1007/s11920-016-0743-9
|View full text |Cite
|
Sign up to set email alerts
|

Schools and Disasters: Safety and Mental Health Assessment and Interventions for Children

Abstract: This article draws on experiences and lessons from global disasters and utilizes the United Nations Comprehensive School Safety Framework to highlight the necessary role of safe schools in protecting children, as well as adult staff, from the immediate threats and long-term implications of disasters. Specifically, we focus on three well-established pillars of school safety: Pillar I: Safe Learning Facilities; Pillar II: Disaster Management; and Pillar III: Risk Reduction and Resilience Education. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 69 publications
3
55
0
Order By: Relevance
“…Schools and school personnel can be instrumental in supporting family interventions [60] and evidenced-based interventions often take place in schools post-disaster [72]. One study found mothers' participation in ongoing therapeutic grief support led to opportunities for increased therapeutic and school support for children with learning disabilities [52•].…”
Section: Family Psychological Treatmentsmentioning
confidence: 99%
“…Schools and school personnel can be instrumental in supporting family interventions [60] and evidenced-based interventions often take place in schools post-disaster [72]. One study found mothers' participation in ongoing therapeutic grief support led to opportunities for increased therapeutic and school support for children with learning disabilities [52•].…”
Section: Family Psychological Treatmentsmentioning
confidence: 99%
“…At the social group level, friend, neighbor, or co-worker relationships may be impacted through the sharing of support and resources and changes in social networks may occur due to displacement [25][26][27]. Finally, at the community level, disruption to normal community functioning from disaster-damaged infrastructure is common such as temporary school closures and reduction in the availability of critical lifelines such as water or electricity services [28,29]. Impacts at each of these levels may also impact food security.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our study discusses mental health assessment tools for potential application following disasters and suggests recommendations for clinical settings. 22)…”
Section: Discussionmentioning
confidence: 99%